Aetiology and epidemiology of fever in children presenting to the emergency department of a French paediatric tertiary care centre after international travel. Issue 2 (11th January 2012) - Naudin, Jérôme; Blondé, Renaud; Alberti, Corinne; Angoulvant, François; De Lauzanne, Agathe; Armoogum, Priscilla; Pull, Lauren; Lorrot, Mathie; Imbert, Patrick; Dauger, Stéphane; Mercier, Jean-Christophe; Faye, Albert
Abstract : Objective: As few data are available on the causes of fever in children returning from international travel, the authors studied children presenting to a French tertiary care centre with fever. Methods: Children presenting to the emergency department of the Robert Debré Paediatric Hospital, Paris, France between July and December 2007 with fever that occurred within 3 months of a stay abroad were included in this retrospective study. Results: The children (n=538) had most commonly visited North Africa (NA) (n=214), sub-Saharan Africa (SSA) (n=185) and Europe (n=67). Their median age was 2.8 years (IQR 1.4–5.8). The median time between their return to France and the onset of fever was 5 days (IQR 0–18). Cosmopolitan infections represented 85% of the established diagnoses (97.8% and 63.9% in the children returning from NA and SSA, respectively). Fever of unknown origin accounted for 19.3% of cases. Malaria was the leading tropical infection. Excluding malaria, diarrhoeal diseases were more frequent in the children returning from NA (38.5%) than in those returning from SSA (24.5%). Malaria was associated with stays in endemic countries that exceeded 30 days (OR 3.13, 95% CI 1.02 to 9.59). Conclusion: Cosmopolitan infections are the leading cause of fever in French children returning from tropical and subtropical areas. However, all febrile children who have returned from an endemic area should be tested for malaria.